The prevalence of pre‐treatment and acquired HIV drug resistance in Vietnam: a nationally representative survey, 2017–2018. Issue 2 (23rd February 2022) - Dat, Vu Quoc; Anh, Nguyen Thi Lan; Van Nghia, Khuu; Linh, Nguyen Thuy; Thu, Huynh Hoang Khanh; Tam, Tran Thi Minh; Ton, Tran; Anh, Luong Que; Phuc, Nguyen Duy; Huong, Phan Thi Thu; Nhan, Do Thi; Hai, Nguyen Huu; et al.
Abstract: Introduction: Monitoring the population‐level emergence and transmission of HIV drug resistance (HIVDR) is necessary for supporting public health programmes. This study provides a nationally representative prevalence estimate of HIVDR in people initiating antiretroviral therapy (ART) and estimates of acquired HIVDR and viral load (VL) suppression in people who have received it for 12 or ≥48 months in Vietnam. Methods: The study was conducted between September 2017 and March 2018 following World Health Organization guidance. Thirty ART clinics were randomly sampled using probability proportional to size sampling from a total of 367 ART clinics in the country. Results and Discussion: In total, 409 patients initiating ART were enrolled into the survey of pre‐treatment HIVDR. The prevalence of any pre‐treatment HIVDR was 5.8% (95% CI 3.4–9.5%), and the prevalence of non‐nucleoside reverse transcriptase inhibitor resistance was 3.4% (95% CI 1.8–6.2%). Four hundred twenty‐nine patients on ART for 12±3 months and 723 patients on ART for ≥48 months were enrolled into the surveys of acquired HIVDR. The prevalence of VL suppression (defined as <1000 copies/ml) in patients on ART for 12±3 and ≥48 months was 95.5% (95% CI 91.3–97.8%) and 96.1% (95% CI 93.2–97.8%), respectively. Among individuals with viral non‐suppression, any HIVDR was detected in 11/14 (weighted prevalence 74.3%) of those on ART for 12±3 months and in 24/27 (weighted prevalence 88.5%) of those receiving ART for ≥48 months. Conclusions: This nationally representative study of HIVDR found high levels of VL suppression among those on ART for 12 and ≥48 months. Overall, high levels of VL suppression at both time points suggested good adherence among patients receiving ART and quality of treatment services in Vietnam. Clinical Trial Number: Not applicable